1996
DOI: 10.1121/1.417211
|View full text |Cite
|
Sign up to set email alerts
|

Measures of tuning and suppression in single-fiber and whole-nerve responses in young and quiet-aged gerbils

Abstract: Tuning and suppression were examined in the auditory nerves of young-control and quiet-aged gerbils. Tuning curves obtained from single-fiber responses were compared to those obtained with the compound action potential (CAP) using masking procedures. Tuning was measured in terms of the high-frequency slope of the tuning curve and Q values obtained 10 dB and 40 dB (Q10 dB and Q40 dB, respectively) above the threshold at its best frequency. The study had two objectives: first, how CAP measures of tuning and supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…In auditory nerve fibres of quiet aged three-year-old gerbils, Schmiedt et al (1990) found that thresholds were elevated by 20-30 dB at the tip (characteristic frequency, CF) of the tuning curves, while the low frequency tails were much less affected, resulting in a reduced tip-to-tail ratio. Measures of frequency selectivity, like Q 10dB and Q 40dB (Hellstrom & Schmiedt, 1996), were similar for young and old gerbils in fibres with CFs below 4 kHz, while auditory nerve fibres with higher CFs were on average less sharply tuned in old gerbils. A comparison of rate-level functions (the discharge rate of auditory nerve fibres plotted as a function of stimulus level) at CF in old and young gerbils showed that these functions in old gerbils were shifted to higher levels, consistent with elevated thresholds of auditory nerve fibres.…”
Section: Activity Of Single Auditory Nerve Fibresmentioning
confidence: 79%
See 4 more Smart Citations
“…In auditory nerve fibres of quiet aged three-year-old gerbils, Schmiedt et al (1990) found that thresholds were elevated by 20-30 dB at the tip (characteristic frequency, CF) of the tuning curves, while the low frequency tails were much less affected, resulting in a reduced tip-to-tail ratio. Measures of frequency selectivity, like Q 10dB and Q 40dB (Hellstrom & Schmiedt, 1996), were similar for young and old gerbils in fibres with CFs below 4 kHz, while auditory nerve fibres with higher CFs were on average less sharply tuned in old gerbils. A comparison of rate-level functions (the discharge rate of auditory nerve fibres plotted as a function of stimulus level) at CF in old and young gerbils showed that these functions in old gerbils were shifted to higher levels, consistent with elevated thresholds of auditory nerve fibres.…”
Section: Activity Of Single Auditory Nerve Fibresmentioning
confidence: 79%
“…The loss of sensitivity was most pronounced at the tip of single-fibre tuning curves and in masked CAP tuning curves (Hellstrom & Schmiedt, 1996) of old gerbils and led to a decreased tip-to-tail ratio of the tuning curves. These changes are similar to the effects of a reduced EP on single-fibre tuning curves in cat (Sewell, 1984).…”
Section: The Gerbil As a Model Of Strial Or Metabolic Presbyacusismentioning
confidence: 99%
See 3 more Smart Citations